2018
DOI: 10.1186/s13756-018-0407-0
|View full text |Cite
|
Sign up to set email alerts
|

View point: gaps in the current guidelines for the prevention of Methicillin-resistant Staphylococcus aureus surgical site infections

Abstract: The authors advocate the addition of two preventative strategies to the current United State’s guidelines for the prevention of surgical site infections. It is known that Staphylococcus aureus, including Methicillin-resistant Staphylococcus aureus (MRSA), carriers are at a higher risk for the development of infections and they can easily transmit the organism. The carriage rate of Staph. aureus in the general population approximates 33%. The CDC estimates the carriage rate of MRSA in the United States is appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The report from the German surveillance network did not examine ceftaroline,22 but the SENTRY program reported that the susceptibility of MSSA to ceftaroline was 100% and that of MRSA was 91.6% 23. For skin and soft tissue infections with suspected MRSA, the guidelines usually recommend oral TMP-SMX, doxycycline, minocycline, and clindamycin, as well as newer agents like linezolid and tedizolid; intravenous vancomycin is the first choice for hospitalized patients, followed by daptomycin when vancomycin cannot be given 1,2426. For bacteremia of suspected MRSA origin, vancomycin and daptomycin are the first choices, followed by ceftaroline combination regimens and teicoplanin 1,27,28.…”
Section: Discussionmentioning
confidence: 99%
“…The report from the German surveillance network did not examine ceftaroline,22 but the SENTRY program reported that the susceptibility of MSSA to ceftaroline was 100% and that of MRSA was 91.6% 23. For skin and soft tissue infections with suspected MRSA, the guidelines usually recommend oral TMP-SMX, doxycycline, minocycline, and clindamycin, as well as newer agents like linezolid and tedizolid; intravenous vancomycin is the first choice for hospitalized patients, followed by daptomycin when vancomycin cannot be given 1,2426. For bacteremia of suspected MRSA origin, vancomycin and daptomycin are the first choices, followed by ceftaroline combination regimens and teicoplanin 1,27,28.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the USA a study reported that the carriage rate of MRSA in healthcare workers approximates 5% with concerns of transmission of this pathogen to patients (13).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently in the USA, Kavanagh et al (2018) reported the carriage rate of S. aureus in the general population approximates 33% and that of MRSA is approximately 2% as estimated by the CDC; still, the carriage rate of MRSA in healthcare workers approximates 5% with concerns of transmission of this pathogen to patients. Also, these recent results reported by Kavanagh et al (2018) are lower than our results regarding S. aureus and MRSA. On the other hand, in Iran, a study was done by Shakeri et al (2010) reported the prevalence of MRSA from healthy carriers and patients as 28%.…”
Section: Discussionmentioning
confidence: 99%